(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article talks about ways of creative and positive development of youth spirituality in modern education. Based on scientific data, the author analyzed the problem on the basis of existing literature and studied the specific aspects of ways of creative and positive development of youth spirituality in the process of modern education.